The presence of iteroparous salmonid spawning grounds affects the stable isotope signatures of food web components in Swedish boreal streams - Rahmat Naddafi; Magnus Enbom; Carin Magnhagen; Nazila Hajizadeh Koupayh; Daniel Holmqvist; Hans Lundqvist (Heliyon)
Marine-derived nutrients (MDN) translocated by anadromous fish can strongly be linked to the dynamics and structure of resident freshwater communities. Yet there is limited knowledge on the transport of marine nutrients by Atlantic salmon (Salmo salar) and sea trout (Salmo trutta) from the Baltic Sea and their incorporation into the trophic system of the boreal streams. Here, stable carbon (δ13C) and nitrogen (δ15N) isotopes were measured in food web components (periphyton, benthic macroinvertebrates, and a predatory fish (freshwater-resident brown trout) of four sites with and without salmonid spawning grounds. Two sites (MDN sites) had spawning Atlantic salmon and sea trout and two other sites (reference sites) had no spawning or mortality areas of these species. A generalized linear mixed model revealed that site type and food web component had a significant effect on δ15N and δ13C values. All food web components studied were enriched with 15N and 13C in MDN sites where the anadromous salmonids spawn and experience high overwinter mortality. The average δ15N and δ13C values were 3.3 ‰ and −23.3 ‰ in periphyton, 4.3 ‰ and −28.9 ‰ in benthic macroinvertebrates, and 7.8 ‰ and −25.7 ‰ in brown trout in MDN sites, respectively. In reference sites, the average δ15N and δ13C values were 1.8 ‰ and −32.7 ‰ in periphyton, 2.0 ‰ and −36.9 ‰ in benthic macroinvertebrates, and 6.5 ‰ and −29.9 ‰ in brown trout, respectively. Upstream migrating Atlantic salmon were more 15N enriched than migrating sea trout. Both Atlantic salmon and sea trout eggs had higher δ15N values and lower δ13C values than their muscles. A Bayesian mixing model revealed variations in the diet of brown trout in different streams. The results from this study show that stream food web components have different isotopic signatures depending on whether iteroparous salmonid spawning/mortality occurs or not.